LANGUAGE POWER IN ADVERTISEMENT INVESTIGATION PERSUASIVE STRATEGIES IN THE SLOGAN PRODUCT “MS GLOW” ON TIKTOK - Dewi Juni Artha; Fanny Fadilla (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2023)
This study deals with the analysis of Persuasive Strategies Used in Slogan product “Ms Glow” on TikTok. Ms Glow is the one famous brand of the beauty from local brand and also every woman uses the product of Ms Glow. It is the reason why the researcher use Ms Glow as an objectin the product can to be the researched. Ms Glow product has a several slogan in advertising their product. The objectives of this research is toidentify the kinds of persuasive strategies and describe the way or modes persuasive strategy used in slogan product of Ms Glow. Qualitativeresearch was applied to analyze the data. That the qualitative research is focused on analyzing the data in the form of words, and not about numerical data. The researcher used 15 slogan advertisement on official account Ms Glow on TikTok. In collecting the data the researcher browsed the slogan advertisement by searching on Ms Glow official account on TikTok, and then the researcher chosen the sloganadvertisement of TikTok to be analyzed. The next, the researcher identified the slogan, understanding what the kinds of persuasive strategiesused in the slogan and the way or modes to persuade consumers. The result of the data analysis show the researcher found and analyzed aboutpersuasive strategies. The types of persuasive strategies, there are: rationalization (5 data), . They are: rationalization (7 data), identification (1data), suggestion (6 data), conformity (9 data) and compensation (1 data). And mostly used in caption is rationalization and conformity. And the way to persuade consumers, those are: ethos (6 data), pathos (5 data) and logos (4 data).